Effects of two successive maximal exercise tests on pulmonary gas exchange in athletes - Caillaud, C. F.; Anselme, F. M.; Prefaut, C. G. (European Journal of Applied Physiology, 1996)
Pulmonary extravascular water accumulation may be involved in exercise-induced hypoxaemia in highly aerobically trained athletes. We hypothesized that if such an alteration were present in elite athletes performing a maximal exercise test, the impairment of gas exchange would be worse during a second exercise test following the first one. Eight male athletes performed two incremental exercise tests separated by a 30-min recovery period. Pulmonary gas exchange and ventilatory data were measured during exercise tests performed in normoxia. Arterial blood samples were drawn each minute during rest, exercise, and recovery. Pulmonary diffusing capacity for CO (DLCO) was measured at rest, after the first (T1) and the second (T2) test. All the subjects underwent a spirometric test at rest and after T2. Maximal and recovery data for O2 uptake and minute ventilation were not statistically different between T1 and T2. Partial pressure of arterial O2 (PaO2) decreased during both tests but was lower during T2 for rest, 60 W, and 120 W (P < 0.02). Alveolar-arterial difference in partial pressure of O2 (PA-aO2) increased during both the tests but was significantly larger during T2 for rest, 60 W, and 120 W (P < 0.01). The PaO2 and PA-aO2 data at maximal exercise were not significantly different between T1 and T2. Compared to rest, PA-aO2 remained significantly larger during recovery for both T1 and T2 (P < 0.0001). The PA-aO2 during T2 recovery was larger than T1 recovery (P < 0.008). Spirometric data did not change. The DLCO measurements after T1 and T2 were not significantly different from rest. These results showed an alteration of PaO2 and PA-aO2 during T1, which tended to be worse during and after T2; however, these data do not allow us to make a definitive statement as to the cause of the hypoxaemia. Our study confirmed that exhausting exercise caused hypoxaemia. It also demonstrated that the disturbance in pulmonary gas exchange persisted for at least 30 min following the end of the exercise period and became worse during submaximal intensities of the following incremental exercise test.